The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/adv.22127
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on activity of cumene hydroperoxide and selected ionic liquids in butadiene rubber vulcanization

Abstract: In this work, cross‐linking at low temperature (90°C) of butadiene rubber (BR) using a vulcanizing system based on a hydroperoxide and ionic liquids (ILs) has been evaluated. Composites of BR with cumene hydroperoxide (CHP) and selected ILs have been prepared and tested. In order to elucidate the influence of novel systems on the cross‐linking as well as on the properties of the final product, BR composites have been characterized by different techniques, that is, rheometrical properties, cross‐linking density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…The results from Table 2 further show that the application of ionic liquids contributed to a slight reduction in the optimum curing time and scorch time of the studied composites. This is in agreement with data in the literature [35], which suggests that ionic liquids may act as catalysts for interface reactions and thereby significantly affect rheometric parameters. In our study, the crosslink density values of the EPM/VMT compounds were found to increase by approximately 2 mol/cm 3 .…”
Section: Curing Measurementssupporting
confidence: 93%
“…The results from Table 2 further show that the application of ionic liquids contributed to a slight reduction in the optimum curing time and scorch time of the studied composites. This is in agreement with data in the literature [35], which suggests that ionic liquids may act as catalysts for interface reactions and thereby significantly affect rheometric parameters. In our study, the crosslink density values of the EPM/VMT compounds were found to increase by approximately 2 mol/cm 3 .…”
Section: Curing Measurementssupporting
confidence: 93%
“…At the same time, the vulcanization time was shortened, as the activation energy of vulcanization was decreased by ILs. Furthermore, ILs catalyzed the interfacial crosslinking reaction to increase the crosslink density [137].…”
Section: Multiple Functions Of Ils In Rubber Vulcanizationmentioning
confidence: 99%
“…Thereby, the increased dielectric permittivity is ascribed to the combined usage of ILB and glycerol. [36][37] According to Equation (2), the 100% increase in dielectric permittivity of S184-gly-ILB-5% is beneficial, in that it increases the Fom(DEA) of transducers. Variations in dielectric losses are presented in Figure 5.…”
Section: Dielectric Properties and Conductivitymentioning
confidence: 99%